Chemical composition of Picea abies and Pinus sylvestris seeds under subarctic conditions - Pulliainen, Erkki; Lajunen, Lauri H. J. (Canadian Journal of Forest Research, 1984)
Seeds produced by 50 Piceaabies L. and 50 Pinussylvestris L. trees near the timberline in eastern Finnish Forest Lapland were collected in late winter 1973–1981, counted, and analysed chemically (specially developed procedure with direct-current plasma emission spectrometry (DCP-AES)). Seed yields, their 1000-grain weights, and their quality varied considerably from year to year in both species, P. abies having good seed yields less often than P. sylvestris (only one good yield during the study period). The mean number of seeds produced by P. abies correlated positively with their 1000-grain weights; in P. sylvestris it did not. The nitrogen, crude fat, sugar, phosphorus, and magnesium contents correlated positively with the corresponding 1000-grain weights, suggesting that these constituents occur mainly in the endosperm and (or) embryo(s) of a seed. The crude fibre and calcium contents, however, correlated negatively with the 1000-grain weights, implying that they occur mainly in the testa. The sodium content did not increase or decrease with increasing 1000-grain weight. The composition of seeds with the same 1000-grain weight but representing yields of different years might also vary. The crude protein proportion in the P. abies seeds produced in different years varied from 9.4 to 19.3%, crude fat varied from 11.0 to 40.2%, and phosphorus varied from 0.30 to 0.83%; the corresponding ranges for P. sylvestris seeds were 10.9–30.9, 7.2–33.5, and 0.42–0.98%, respectively. Some aspects of defensive strategies of sympatric pine and spruce stands under hostile conditions at the timberline are discussed.